Increasing Diversity in Orthopaedic Surgery Residency - Hans K. Owuor, BS; Eric J Strauss, MD, FAOA; Toni McLaurin, MD, FAOA; Joseph D Zuckerman, MD, FAOA; Kenneth A. Egol, MD, FAOA (JBJS Open Access)
Introduction:. African American, Hispanic, Asian, and Pacific Islanders are groups who are underrepresented in medicine (URM groups). Similarly, although women comprise more than 50% of medical students in the United States, women comprise a smaller percentage of all orthopaedic surgery trainees. Therefore, underrepresented in orthopaedics (URiO) represents the URM groups and women. The purpose of this study is to examine the impact of specific steps to recruit a qualified, diverse trainee complement within a single academic orthopaedic surgery residency program between 2000 and 2023. We aim to explore changes in the representation of URiO during this period as well as explore the strategies and programs implemented by the department that may have impacted recruitment of a diverse complement of trainees. Methods:. Match lists from a large, academic, orthopaedic surgery residency between 2000 and 2023 were collected and reviewed for racial and gender data. Match lists were then divided into 6-year quantiles to identify any trends in the recruitment of URiO students. Self-reported racial and gender data from Electronic Residency Application Service applicant reports and the Accreditation Council for Graduate Medical Education (ACGME) data books between 2018 and 2022 were collected and reviewed. In addition, the department's strategies implemented during the study period with the goal of enhancing URiO exposure to orthopaedic surgery were also explored. Results:. The department implemented proactive strategies to increase exposure to orthopaedic surgery for URiO students. An increase in URiO representation was noted between 2000 and 2023 with Hispanic, Black/African American, and Native Hawaiian/Pacific Islander resident representation increasing by 5%, 11%, and 1%, respectively. In addition, women representation increased by 27% between 2000 and 2023. The overall attrition rate among URiO residents was 1% with only one resident not completing the program. Self-reported racial and gender data from ACGME data books demonstrated that Black/African American, Hispanic, and Native Hawaiian/Pacific Islander residents comprised 5%, 4%, and 0.04%, respectively, of orthopaedic surgery residents between 2018 and 2022. Conclusions:. These results provide insight for other programs to use similar strategies to potentially improve recruitment, retain, and provide support to URiO residents.